The Use Of Moodle-Based E-Learning In Evaluating Students’ Learning - Triyana, I Gusti Ngurah; Sri Ratmini, Ni Ketut; Mandra, I Wayan; Ruscitadewi, Ni Wayan (Jurnal Penjaminan Mutu, 2019)
Education is a very important thing in Indonesia. It is the main concern of this nation, because education will determine the direction of progress of a nation. Education is a conscious and planned guidance from educators on the physical and spiritual development of students towards the formation of humans who have the main knowledge and personality. In the process of education, science must be owned by educators and taught to students so that it will be able to be absorbed and developed more optimally. To find out the success or failure of the guidance received by students, it is necessary to conduct an evaluation to find out the development of knowledge taught by the teacher. In teaching, successful evaluation determines the steps that can be taken by students and teachers in knowing the development and improving the quality of education in the future. Currently technological advances have a direct impact on the world of education where e-learning-based teaching becomes an option that can support and teach students in developing materials and abilities in the field of technology. Moodle is one of the evaluation programs that use technological progress to facilitate and teach students to get to know more about technological progress.